1851 Ky. Acts 296 - (:unkn) unknown (My University, 1851)
Of Dealing With Slaves and Suffering Them to go at Large,§ 12: Prohibited "any negro" from keeping or carrying a gun, weapon, powder, or shot.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES